Analisis Laporan Arus Kas untuk Menilai Kinerja Keuangan Perusahaan pada Bank BCA Syariah - Ahmad Fauzul Hakim Hasibuan; Alpi Sahrianti Ritonga; Intan Mutia; Sridevi Lumban Batu (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2023)
A good company must have a stable or ideal cash flow. The ideal cash flow condition is when the incoming and outgoing cash flows are balanced. However, there are three problems that can cause non-ideal cash flow, namely cash flow deficit problems, cash flow problems, and cash flow surplus problems. If cash inflows are less than cash outflows, the company will face an unprofitable cash deficit problem. The purpose of this study is to determine the level of cash flow statements to assess financial performance at Bank BCA Syariah. the discovery procedure was carried out without using statistical or quantitative methods. The results of the study show that the financial performance of PT Bank BCA Syariah from 2019 to 2022 both in terms of cash ratios, ROE, ROA and ROI is quite good and reliable. The company's ability to manage cash, equity, total assets and investments also looks good. However, it is necessary to watch out for profit turnover and total asset turnover which need further attention. Keywords: Cash Flow, Financial Performance